Paper collage workshop - Price, Samuel (Walter Foster Publishing, 2022)
Paper Collage Workshop enables mixed media artists, DIYers, crafters, and aspiring artists to explore their artistic side without having to invest in a range of expensive art tools and supplies. The only things required to play are scissors, paper, glue, and imagination!